Making market-based redispatch efficient: How to alter distribution effects without distorting the generation dispatch? - Martin Palovic (Jacobs University Bremen, Bremen Energy Research (BER), 2022)
Market-based redispatch is efficient in short-run but provides perverse long-run incentives. This paper explains such incentives by distribution effects of the tool. Therefore, market-based redispatch is conceptualized as a Coasean bargaining about network capacity. This allows altering distribution effects without impeding the short-term efficiency. Two design adjustments are derived. First, long run incremental cost is introduced next to market-based redispatch, as in the UK. Perverse incentives are removed but the long-run optimum is missed. Second, interruptible network connections with secondary market, known from the gas sector, replace market-based redispatch. This solution is efficient in the short- and long-run.
Keywords: 330